Blue Economy: Solusi Membangun Kembali Perekonomian “Blue Recovery” Pasca Pandemi Covid-19 untuk Sustainable Welfare - Ilma, Ajeng Faizah; Supriadi, Dedi (Lingka Ekonomika, 2022)
Indonesia has great potential to carry out a recovery based on maritime sector after the Covid-19 pandemic (Blue Recovery) and encourage the transition from extractive efforts to the creation of added value and productivity. The blue economy is also a space to create new innovations and creativity, both in existing and developing sectors, so that the blue economy can be a driver of inclusive welfare improvement. Several issues were raised as an alternative solution to the economic downturn during the Covid-19 pandemic in Indonesia. The blue economy is expected to bring sustainable prosperity to coastal communities in Indonesia as well as people who depend on the marine sector for their livelihoods. The blue economy is the main issue of environmentally sound marine resources to support economic growth, sustainable prosperity and livelihood stability as well as the preservation of marine ecosystems with clean, no waste, sustainable use of ocean resources for economic growth, improved livelihoods, and jobs while preserving the health of ocean ecosystem.